Mexico and the food self-sufficiency (six-year period 2006 -2012) (2014)
Today, Mexico challenges a globalization trend where richer countries export basic products to developing countries, generating a food crisis that negatively affect the medium-small producers. For this reason, it is important to study the behavior of the food market (exports and imports), since the current Mexican development model does not achieve that food security be a national policy guaranteeing the provision of food for the entire population. Specifically, this article analyses the performance of the food situation during the six–year period 2006-2012, studying three basic foods for Mexican population (maize, bean, wheat) and others strategic food like sugar, sorghum and soy. In addition, it analyzes the performance of harvesting and sowing surface, exports and imports. Results indicated that the three main foods showed had high import growth rates decreasing national harvest and sowing surface, with a trade balance deficit during the six-year period studied. The conclusion is that the local producers need a change in the production dynamics and play a strategic role in the food production with new sustainable alternatives.